Household response to an extreme shock: Evidence on the immediate impact of the Covid-19 lockdown on economic outcomes and well-being in rural Uganda - Mahmud, Mahreen; Riley, Emma (World development, 2021)
•Compared to immediately before the lockdown, household income falls by 60%, with enterprise and wage income heavily hit.•Households respond by purchasing 50% less food per capita.•Households draw down their savings and increase borrowing, but have not yet sold fixed assets.•Households increase their labour supply to the farm and livestock, more than the decline to enterprises and wage labour.•Well-being declines: 50% increase in the likelihood of missing a meal and 25% decline in reported life satisfaction. We provide evidence on the economic and well-being impact of the Covid-19 lockdown on a sample of households in rural Uganda. Our sample consists of 1,277 households randomly drawn from 114 rural villages in western Uganda and surveyed in-person in early March 2020, just before the lockdown. We followed up with this sample in May 2020, reaching over 85% of them by phone. We find a large decline of 60% in household non-farm income due to household enterprise profits and labour income being almost wiped-out post the lockdown. Households respond to this loss of income in three key ways. One, there is a 40% decrease in food expenditure per adult equivalent. Two, they use up nearly 50% of their savings and borrow more, but have not yet liquidated their fixed assets or sold livestock. Three, they increase total household labour supply to household farm and livestock, more than making up for the decline in supply to enterprises and labour outside the household. We find a decrease in well-being as a result of this: there is an increase in the likelihood of missing a meal, a decline in reported satisfaction with quality of life, a higher likelihood of having a major argument with their spouse and an increase in perceived frequency of intimate partner violence against women in the village. The negative effects of the lockdown are greater for households that were wealthier at baseline, since these households were more reliant on enterprise and salaried income. These results were one of the first to show a large negative impact of the lockdown for a rural population. Our findings are important to policy makers in Uganda and other developing countries as they suggest income and consumption support is needed for rural households.